The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1177/14644207221149861
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behavior of tribo-pairs in water hydraulic radial piston pumps

Abstract: Friction and wear tests were performed on five Cu-based materials and three polyether ether ketone (PEEK)-based composites sliding against 17-4PH and 42CrMo4 coated with tungsten carbide-reinforced Ni-based coating. Two types of pin-on-disk specimens were used to represent the slipper/eccentric drive and piston/sleeve gap seal tribo-pairs in water hydraulic radial piston pumps. The experimental results showed that the QSn8-0.3 slipper material exhibited the highest steady-state friction coefficients for slidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The angle between line AO j j and the horizontal line is a, and the angle between line BO j j and the horizontal line is u 2 . Based on the structural dimensions, angles b and g are equal to 2 7 p. Therefore, angles a and u 2 can be obtained using equations ( 3) and (4), respectively:…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The angle between line AO j j and the horizontal line is a, and the angle between line BO j j and the horizontal line is u 2 . Based on the structural dimensions, angles b and g are equal to 2 7 p. Therefore, angles a and u 2 can be obtained using equations ( 3) and (4), respectively:…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Water hydraulic radial piston pumps (RPPs) have the advantages of excellent anti-noise characteristics, low pulsation, and reduced leakage and are widely used to transmit high pressure and power in various industrial applications, [1][2][3] such as seawater desalination, descaling, and coal mining. According to the different drive ends, RPPs can be divided into two typical types 4 : rotary cylinder blocks and eccentric cams.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al 16 showed that the density of the tribopair material has a greater effect on the COF than Poisson's ratio or modulus of elasticity. Li et al 17 examined the effect of the material hardness and product of pressure and velocity (PV) value on the tribological behaviour of the tribopairs in a water hydraulic radial piston pump. Lysykh et al 18 found that surface hardening with boron and copper enhanced the mechanical properties of AISI L6 and 5140 steels and significantly increased their wear resistance.…”
Section: Introductionmentioning
confidence: 99%